Warstwa werbalna ścieżki dźwiękowej jako element współbudowania przestrzeni w filmie - Skowronek, Bogusław (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The article presents the most typical ways of co-building various types of film space through the verbal layer of the soundtrack: inside the frame and outside of it, diegetic and non-diegetic, and narrative and non-narrative. In order to discuss linguistic ways of co-creating space, the author used the tenets of mediolinguistics and the ideas of the textual image of the world and the linguistic image of the world.